Community Ownership of Local Assets: conditions for sustainable success. (January 2019) - Hobson, Jonathan; Lynch, Kenny; Roberts, Hazel; Payne, Brian
Highlights: Transferring assets to local community management is one way in which Local Authorities have been dealing with the pressures of austerity, and transferred assets may provide more targeted and responsive community services. Asset transfer may increase a community's sense of ownership over a community asset although communities with different resources may benefit unequally from asset transfer. The success of a community asset depends on a meshing of forms of capital, with physical assets providing 'social infrastructure': a location for the generation and performance of other forms of capital. There is a tension in asset transfers between a forced responsibilisation of communities that might not be equipped to manage, and the conditions required for generating 'collective responsibility'.